History of Rabies in the Americas: From the Pre-Columbian to the Present, Volume I Insights to Specific Cross-Cutting Aspects of the Disease in the Americas - Rupprecht, Charles E. (Cham : Springer International Publishing : Imprint: Springer, 2023)
Rabies is one of the oldest known pathogens, is incurable, and has the highest fatality rate of all infectious diseases. The Americas is the only region with bat rabies virus, including vampire bat rabies. The region is rich in cultural references and notable for many discoveries in the field, including the current vaccine potency test, diagnostic assay, conception of oral vaccines for wildlife, the first human survivor and the first successful canine rabies program executed at a broad level. Rabies remains the most important viral zoonosis, with tens of thousands of human fatalities and tens of millions of exposures annually, which can be used to model for other pathogens, such as COVID-19. There is an international effort to eliminate human rabies caused by dogs over the next decade, and the Americas represent the primary region with the greatest proof-of-concept evidence to accomplish this goal. This two-volume set addresses the medical history and modern results of rabies in countries throughout the Americas, including the implications of and on cultural, economic, sociological, and research developments in the region. Volume I presents an overview of concepts critical to the study of rabies in the region, including evolutionary aspects, reservoir ecology and control, elimination efforts, vaccine development, and disease hallmarks and progression. It also analyzes the long-term cultural, social, and economic impacts of the disease in the Americas. .
The world in flux - the Columbian Exchange D. Domenici -- Glimpses into the past: new world contributions towards understanding the basic etiology, pathobiology & treatment of rabies, Drishya Kurup et al -- The Diversity, Evolution and Emergence of Rabies Virus in the Americas, Edward C. Holmes & Erin H. Harvey -- The ecological range and principles of wildlife rabies virus perpetuation in the Americas, Amy T. Gilbert -- Historical Laboratory Contributions Supporting Rabies Diagnosis and Disease Prevention and Control in the Americas, Susan A. Nadin-Davis, et al -- Progression from nerve tissue vaccines to recombinant biologics, H. Ertl -- Wildlife Rabies Management in the New World: Prevention, Control and Elimination in Mesocarnivores, R. Chipman et al -- Management of vampire bats and rabies: past, present, and future, Tonie Rocke & Daniel Streicker -- Conflicting Perspectives on a Rabies Outbreak in a Venezuelan Rainforest, 2007-2008, C. Briggs -- Rabies, Medicine, and Culture: Dogs, Disease, and Urban Life in the United States, 1840-1920, Jessica Wang -- Historical disparities in health: rabies surveillance, risk factors and prevention, Amira Roess et al -- The Health Economics of Rabies in the Americas: An Historical Summary and a Synthesis of the Literature, S.A. Shwiff -- Towards the elimination of canine rabies in the americas: governance of a regional program, M. Vigilato et al -- Musing Over Non-technical Criticalities of Rabies Prevention and Control in the Americas, Victor J. Del Rio Vilas & Gilberto Montibeller.
Keywords: Immunology; Virology; Medicine -- History; Veterinary medicine; Vaccines -- Biotechnology; Biomaterials; Immunology; Virology; History of Medicine; Veterinary Science; Biomaterials-Vaccines.